2021
DOI: 10.1002/adhm.202100601
|View full text |Cite
|
Sign up to set email alerts
|

Nanozyme with Robust Catalase Activity by Multiple Mechanisms and Its Application for Hypoxic Tumor Treatment

Abstract: Utilizing catalase-mimicking nanozymes to produce O 2 is an effective method to overcome tumor hypoxia. However, it is challenging to fabricate nanozymes with ultrahigh catalytic activity. Palladium nanosheet (Pd NS), a photothermal agent for photothermal therapy (PTT), has superior catalase-mimicking activity. Here, titanium dioxide (TiO 2 ) is used to modify Pd NS (denoted Pd@TiO 2 ) by a simple one-step method to improve its catalytic activity about 8 times. The enhancement mechanism's fundamental insights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 51 publications
(27 reference statements)
1
47
0
Order By: Relevance
“…To mimic the enzymatic activity of CAT, many metalcontaining and carbon-based nanomaterials have been developed [83][84][85][86][87][88][89][90][91]. For instance, Dan and coworkers designed indocyanine green-loaded ultrasmall gold nanoclusters (Au NCs-ICG) that had a similar catalytic capability to CAT but not POD or SOD (Fig.…”
Section: Cat-like Nanozymesmentioning
confidence: 99%
“…To mimic the enzymatic activity of CAT, many metalcontaining and carbon-based nanomaterials have been developed [83][84][85][86][87][88][89][90][91]. For instance, Dan and coworkers designed indocyanine green-loaded ultrasmall gold nanoclusters (Au NCs-ICG) that had a similar catalytic capability to CAT but not POD or SOD (Fig.…”
Section: Cat-like Nanozymesmentioning
confidence: 99%
“…By comparing the decomposition of H 2 O 2 on Pd NS and Pd@TiO 2 , it is found that the decomposition of H 2 O 2 on Pd@TiO 2 releases more heat and has higher activity. [78] To sum up, the catalytic reaction mechanisms of H 2 O 2 decomposition catalyzed by metal and metal oxides as CAT-like nanozymes are presented. The catalytic mechanisms of CAT-like enzymes can be divided into homolytic and heterolytic paths, which are determined by RDS.…”
Section: Homolytic Catalytic Mechanismmentioning
confidence: 99%
“…Utilizing intrinsic CAT-like activity, PTZCs catalyze the decomposition of H 2 O 2 to O 2 , thereby improving tumor hypoxia and further enhancing the synergistic efficiency of PTT and PDT both in vivo and in vitro. [78] For enhancing combination of PDT/PTT tumor therapy, Li et al synthesized Pt-Ce6 nanocomposites. It has been demonstrated that this versatile Pt-Ce6 nanoplatform exhibits superior CATlike activity, thus continuously and stably decompose H 2 O 2 into oxygen, thereby alleviating tumor hypoxia and improving the synergistic therapeutic effect of PDT and PTT in vitro or in vivo.…”
Section: Tumor Therapymentioning
confidence: 99%
“…Recently, the employment of metal-based materials to promote the decomposition of tumor endogenous H 2 O 2 to generate oxygen has attracted increasing attention. Titanium dioxide-modified palladium (Pd) nanosheets [ 123 ], Pd nanoparticles [ 124 ], defective cobalt (Co) hydroxide [ 125 ], Co 3 O 4 nanoparticles [ 126 ], iridium (Ir) oxide [ 127 , 128 ], cerium (Ce) oxide nanoparticles [ 129 , 130 ], platinum (Pt) nanozyme [ 131 , 132 ], gold (Au) nanoclusters [ 133 ], iron (Fe)-based materials [ 134 , 135 , 136 , 137 , 138 ], etc. have been used to accelerate the decomposition of H 2 O 2 to generate oxygen.…”
Section: Strategies For Modulating Tumor Hypoxia In Pdtmentioning
confidence: 99%